Multi-Omics Analysis Identifies Immune Regulatory Networks in Sepsis-Associated Liver Injury: Experimental Validation and Clinical Relevance - Hong Y; Chen Q; Xie H; Ma M; Gan S; Zhang Y; Xu Z (Journal of Inflammation Research)
Yiyu Hong,* Qiutong Chen,* Hua Xie, Mingliu Ma, Siting Gan, Yuqi Zhang, Zhaozhong Xu Department of Emergency, Zhujiang Hospital, Southern Medical University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhaozhong Xu, Email xzz1008@163.comPurpose: Sepsis-induced liver injury (SILI) significantly contributes to mortality, yet its underlying immune mechanisms remain poorly understood. This study aimed to identify key immune-related genes (IRGs) driving T cell-mediated responses in SILI and evaluate their diagnostic potential.Methods: Cecal ligation and puncture (CLP) was performed to establish a murine sepsis model (n=7/group), with sham-operated controls. Serum IL-1β and lactate levels were quantified via ELISA. Public transcriptomic datasets (GSE26440, GSE26378, GSE25504, GSE28750; 180 sepsis vs 53 controls) were analyzed to identify differentially expressed IRGs (DEIRGs). Functional enrichment (GO/KEGG), protein-protein interaction (PPI) networks, and single-cell RNA sequencing (scRNA-seq) were integrated to prioritize T cell-associated genes. Flow cytometry assessed immune cell subsets (CD3+ T cells, CD19+ B cells, NK1.1+ NK cells, F4/80+ macrophages) in murine blood. Liver histopathology (HE staining) and cytokine expression (IL-1β/TNF-α; IHC) were evaluated.Results: CLP mice exhibited elevated IL-1β (P< 0.01) and lactate (P< 0.01), confirming metabolic dysfunction and inflammation. Bioinformatics analysis identified 19 DEIRGs, with PPI networks implicating immune regulation (PPI enrichment p=3.35× 10-6). Flow cytometry confirmed T cell dominance (65.87% vs 63.85% in controls). scRNA-seq revealed four T cell-linked hub genes (FCER1G, IL2RB, PTGDR, XCL1). Protein-protein interaction (PPI) network analysis demonstrated that these genes form a synergistic regulatory network involving NF-κB, JAK-STAT, and other key pathways, with notable features including the IL2RB-XCL1 positive feedback loop and the opposing effects of PTGDR isoforms (DP1/DP2). Histopathology showed hepatic necrosis and inflammatory infiltration, correlating with upregulated IL-1β/TNF-α (IHC, P< 0.05).Conclusion: FCER1G, IL2RB, PTGDR, and XCL1 are novel T cell-related biomarkers of SILI, offering potential therapeutic targets. The study bridges bioinformatics predictions with experimental validation, advancing understanding of immune dysregulation in sepsis.Keywords: sepsis, acute liver injury, immunity, T cells, RNA single cell sequencing